Chromium (VI)-Induced Alterations in Physio-Chemical Parameters, Yield, and Yield Characteristics in Two Cultivars of Mungbean (Vigna radiata L.) - Singh, Deepti; Sharma, Nathi Lal; Singh, Chandan Kumar; Yerramilli, Vimala; Narayan, Rup; Sarkar, Susheel Kumar; Singh, Ishwar (Frontiers in Plant Science, 2021)
Chromium (Cr) contamination of soil and water resources and its toxicity has adversely affected plant growth and crop productivity. Here, we evaluated the deleterious effects of different levels of Cr (VI) treatments i.e. 0, 30, 60, 90, and 120 µM on two mungbean cultivars, Pusa Vishal and Pusa Ratna, in hydroponic and pot conditions. Germination, seedling growth, biomass production, antioxidant enzyme, electrolytic leakage, oxidative stress (hydrogen peroxide and malondialdehyde), and proline content were determined to evaluate the performance of both cultivars under hydroponic conditions for 15 days. The hydroponic results were further compared with the growth and seed yield attributes of both the genotypes in pot experiments performed over two years. Seedling growth, biomass production, total chlorophyll (Chl), Chl-a, Chl-b, nitrogen content, plant height, seed protein, and seed yield decreased significantly under the 120 µM Cr stress level. Activities of antioxidant enzymes superoxide dismutase, catalase, ascorbate peroxidase and peroxidase increased in the leaves following Cr exposure at 60–90 µM but declined at 120 µM. Cr-induced reductions in growth and seed yield attributes were more in the sensitive than in the tolerant cultivar. Cr accumulation in the roots, stems, leaves, and seeds increased with an increase in Cr concentrations in the pot conditions. Furthermore, for both cultivars, there were significant negative correlations in morpho-physiological characteristics under high Cr concentrations. Overall, our results suggest that Pusa Ratna is more sensitive to Cr stress Pusa Vishal at the seedling stage and in pot conditions. Furthermore, Pusa Vishal can be utilized to study the mechanisms of Cr tolerance and in breeding programs to develop Cr-resistant varieties.